2014
DOI: 10.1074/jbc.m114.550038
|View full text |Cite
|
Sign up to set email alerts
|

The Prolyl Peptidases PRCP/PREP Regulate IRS-1 Stability Critical for Rapamycin-induced Feedback Activation of PI3K and AKT

Abstract: Background: Prolylcarboxypeptidase (PRCP) and prolyl endopeptidase (PREP) regulate proliferation and survival of breast cancer cells. Results: PRCP and PREP regulate IRS-1 stability and PI3K/AKT activation in pancreatic cancer cells. Depletion/inhibition of PRCP/PREP suppresses rapamycin-induced activation of PI3K/AKT with consequent additive/synergistic cytotoxicity. Conclusion: PRCP and PREP regulate IRS-1 stability and PI3K/AKT activation in pancreatic cancer. Significance: Prolyl peptidases are potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Regarding the constituents of JSD, Rhubarb is a herb commonly used in traditional medicine for diarrhea, removing stagnancy, heat clearing, fire draining, detoxicating, promoting blood circulation, and removing blood stasis; therefore, this herb is useful for clearing heat and relieving turbidity in DN. The literature [14,23,24] has reported that this herb has good antidiabetic effects. Liquorice is a sweet-natured herb and is clinically applied as a classical adjuvant herb in many prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the constituents of JSD, Rhubarb is a herb commonly used in traditional medicine for diarrhea, removing stagnancy, heat clearing, fire draining, detoxicating, promoting blood circulation, and removing blood stasis; therefore, this herb is useful for clearing heat and relieving turbidity in DN. The literature [14,23,24] has reported that this herb has good antidiabetic effects. Liquorice is a sweet-natured herb and is clinically applied as a classical adjuvant herb in many prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that IRS-1 is an important growth-regulatory adaptor molecule which plays a role in cell proliferation. Prolylcarboxypeptidase and prolylendopeptidase-mediated stabilization of IRS1 is critical for PI3K/Akt signaling is associated with development and clinical aggressiveness of pancreatic cancer (48). Moreover, IRS1 is highly expressed in localized breast tumors and regulates the sensitivity of breast cancer cells to chemotherapy (49).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin stimulation partially inhibits IRS1-CD36 association via decrease of CD36 ubiquitination, which leads to IRS1-CUL7 interaction and IRS1 degradation. In the absence of CD36 or expression of CD36-K/A which does not bind to IRS1 well, IRS1 interaction with CUL7 was enhanced, leading to accelerated by guest on May 8, 2018 …”
Section: Figure 3 Cd36 Alleviates Insulin-induced Degradation Of Irs-1mentioning
confidence: 99%
See 1 more Smart Citation
“…The main function of POP was previously thought to be the preferential hydrolysis of peptides containing <30 amino acid residues in the extracellular space, such as substance P, thyrotropinreleasing hormone and gonadotrophin-releasing hormone (Friedman & Wilk, 1985;Toide, Okamiya, Iwamoto, & Kato, 1995). However, an increasing number of studies have shown that POP also plays important roles in many intracellular processes, such as the cell cycle (Sakaguchi, Matsuda, Matsumura, Yoshimoto, & Takaoka, 2011), signal transduction (Duan et al, 2014), protein maturation (Morawski et al, 2011), and intracellular transport (Morawski et al, 2011). POP also affects numerous pathological and physiological processes by regulating cell differentiation, proliferation, and apoptosis (Matsuda et al, 2013;Suzuki et al, 2014).…”
Section: Sf1 Contributes To the Regulation Of Progesterone Synthesimentioning
confidence: 99%